Quiet Quitting Due to Work Stress, Mediated by Job Satisfaction and Affective Commitment - Ilham Attamimi; Majang Palupi (Universitas KH. Abdul Chalim Mojokerto, 2025)
The formulation of the problem in this study is the extent to which job satisfaction and affective commitment mediate the relationship between job stress and quiet retirement in Awal Bros Hospital Pekanbaru, Riau. This study involved nurses from Awal Bros Hospital Pekanbaru as research subjects. From the conducted research, there are 45 pieces of data that can be processed for further analysis. In this study, SEM technique was used as an analytical tool with SmartPLS 3 to test the data. The findings of this study show that job satisfaction has a significant effect on quiet quitting, while work stress has a negative but insignificant effect on quiet quitting. Affective commitment of the nurses had a significant positive effect on silent quitting. Work stress that nurses experience has a positive effect on their job satisfaction, but a negative effect on their affective commitment. As mediating variables, job satisfaction and affective commitment may mediate the relationship between job stress and quiet quitting. This research can be a future reference point in solving the problem of silent quitting that exists in the working environment by reducing employees' work stress levels and increasing job satisfaction and affective commitment among employees.